2022
DOI: 10.3390/molecules27155020
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Hydrothermal Rapid Synthesis of Ultralong Hydroxyapatite Nanowires Using Adenosine 5′-Triphosphate

Abstract: Ultralong hydroxyapatite (HAP) nanowires are promising for various biomedical applications owing to their chemical similarity to the inorganic constituent of bone, high biocompatibility, good flexibility, excellent mechanical properties, etc. However, it is still challenging to control the formation of ultralong HAP nanowires because of the presence of free PO43− ions in the reaction system containing the inorganic phosphate source. In addition, it takes a long period of time (usually tens of hours) for the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…In addition, the aerogels and porous materials constructed from self-assembled ultralong hydroxyapatite nanowire bundles exhibit the combination of high porosity and good mechanical properties, and therefore are promising for a wide range of applications. 35,[399][400][401][402][403][404][405] Achieving large-sized highly ordered self-assembly of 1D nanostructures is a great challenge because of the tendency of 1D nanostructures especially ultralong nanowires to become tangled and aggregated. Chen et al 372 reported a strategy for the rapid automated production of highly flexible, large-sized, self-assembled highly ordered ultralong hydroxyapatite nanowires by simply injecting the as-prepared solvothermal product slurry containing ultralong hydroxyapatite nanowires into absolute ethanol or other alcohols at room temperature.…”
Section: Mechanical Enhancementmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the aerogels and porous materials constructed from self-assembled ultralong hydroxyapatite nanowire bundles exhibit the combination of high porosity and good mechanical properties, and therefore are promising for a wide range of applications. 35,[399][400][401][402][403][404][405] Achieving large-sized highly ordered self-assembly of 1D nanostructures is a great challenge because of the tendency of 1D nanostructures especially ultralong nanowires to become tangled and aggregated. Chen et al 372 reported a strategy for the rapid automated production of highly flexible, large-sized, self-assembled highly ordered ultralong hydroxyapatite nanowires by simply injecting the as-prepared solvothermal product slurry containing ultralong hydroxyapatite nanowires into absolute ethanol or other alcohols at room temperature.…”
Section: Mechanical Enhancementmentioning
confidence: 99%
“…In addition, using the advantage of rapid heating of microwave irradiation, the temperature of the reaction system can be quickly raised to a specific value, effectively reducing side reactions and forming uniform size and morphology. Zhang et al 402 used adenosine 5 0 -triphosphate as the phosphorus source and applied the microwave-assisted calcium oleate precursor method to synthesize ultralong hydroxyapatite nanowires. Adenosine 5 0 -triphosphate molecules would not hydrolyze in an aqueous solution at room temperature, and no free PO 4 3À ions existed in the reaction system, avoiding the premature chemical reaction between the calcium oleate precursor and PO 4 3À ions (Fig.…”
Section: 123mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the organophosphorus esters were used as organic phosphorus sources to prepare AP hybrid materials by solvothermal methods. Adenosine 5-monophosphate sodium salt (AMP) [7], pyridoxal-5'-phosphate (PLP) [8], beta-glycerophosphate disodium salt (BGP) [9], adenosine 5'-diphosphate (ADP) [10], adenosine 5'triphosphate (ATP) [11], cytidine 5'-triphosphate disodium salt (CTP) [12] and fructose 1,6-bisphosphate trisodium salt (FBP) [13] biochemical reagents were used to synthesized AP materials. However, because of the weak coordination between AP and the organic raw material after hydrolysis of phosphate ester, the materials obtained in the literature are basically AP inorganic materials without organic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The previous literature, including our preceding studies, has predominantly been confined to specific aspects such as the impact of the initial Ca/P ratio and initial pH on the microstructure and phase of HA nanofibers. ,, Even the latest reports primarily focus on the influence of fatty acid molecules and phosphorus sources on the microstructure of HA nanofiber. , There has been a lack of systematic exploration into the nucleation and crystal growth processes of HA nanofibers synthesized by the oleic acid-assisted solvothermal method. Therefore, in our present work, the evolution process of the microstructure and composition of HA nanofibers is studied in detail based on variations in solvothermal time and temperature.…”
Section: Introductionmentioning
confidence: 99%